Model Imagination, originality and expression in the development of creativity of Peruvian university students (GnosisWisdom, 2022)
It is a rehearsal on a model of development of the creativity that highlights the importance of the process of separating to a side what has been learned up to now to restart and to be able to truly learn, to learn how to imagine. The ideal of learning along a lifetime it will only be reality when the initial formation of the youths is centered more in the happiness of discovering, to question and to imagine; in the "alearning" challenge the routines to learn how to be, to create and, mainly, to cohabit with their neighbors. The teacher has to be willing to reinvent and to learn again with his students and he will discover this way new things. The model "IOE" is a program based directly on the works carried out by Guilford and Torrance; it tries to individualize and to humanize the learning process; it supposes an innovation in education and it seeks, more than to encourage the students to develop their creativity, to show them the roads of how to make it. The pattern consists of a square of capacities that the student has to dominate, in each area of the curriculum, with the objective of stimulating the creativity.
Keywords: Creativity; model; rehearsal